Student’s olympiad EUROPE 2007 - Dzindzalieta, Dainius (Lietuvos matematikos rinkinys, 2021)
Problems of a students olympiad EUROPE 2007 are considered. The problems are given in English and Lithuanian. Two solutions of problems are proposed.